Is chronic rhinosinusitis related to allergic rhinitis in adults and children? Applying epidemiological guidelines for causation. Issue 7 (12th May 2014) - Georgalas, C.; Vlastos, I.; Picavet, V.; van Drunen, C.; Garas, G.; Prokopakis, E.
Abstract The relationship between allergic rhinitis and chronic rhinosinusitis has been assessed in a number of observational and experimental studies. In this review, we attempt their synthesis and evaluation using the modified Bradford Hill guidelines for causation. Although there is no proof of causation, especially in the pediatric literature, an evaluation of underlying allergies is recommended at least as an initial measure of symptoms relief.